Subjectivity and professional vocational counselling - Müller, Marina (2004)
In this work, I shall deal with the psychodynamic approach to subjectivity in P.V.C. To this effect, I want to develop the concept of subject and subjectivity, its variation and historical-social construction and its approach in counselling, from a psychodynamic conceptual framework in P.V.C. with a short reference to the theoretical sources on which this approach is founded.